Borderline personality disorder: part 1 – assessment and diagnosis. (May 2020) - Garland, Jacqueline; Miller, Stephen
SUMMARY: General adult psychiatrists are largely responsible for the care of patients with personality disorders in community and in-patient settings, and this can be associated with diagnostic and management challenges. In the first of two articles focusing specifically on borderline personality disorder (BPD), we summarise the core clinical features of the disorder and discuss appropriate diagnostic practice.